Bankruptcy Implementation in Savings and Credit Cooperatives as Instruments for Transformation and Microfinancial Institution Strengthening - Sugeng, Sugeng; Fitriana, Diana; Romasindah Aidy, Widya; Ryul Park, Kyung (Faculty of Law, Universitas Negeri Semarang, 2023)
This article examines the important role of bankruptcy implementation in savings and credit cooperatives as instruments for the transformation and strengthening of microfinancial institutions. The sustainability and development of microfinancial institutions have significant implications for financial access for low-income communities. However, financial risks and operational challenges often hinder the optimal performance of savings and credit cooperatives. In this context, this article highlights the strategic value of bankruptcy concept implementation as a means of transformation and empowerment for microfinancial institutions. The concept of bankruptcy implementation in the context of savings and credit cooperatives demonstrates how concrete steps can be taken to carry out the bankruptcy process. Legal aspects, debt restructuring processes, and asset protection become important focal points in addressing financial challenges. The article also addresses potential challenges that may arise in bankruptcy implementation, such as costs, complexity, and reduced trust from relevant parties. However, through comprehensive analysis, this article identifies mitigation steps that can be taken to overcome these constraints. Referring to real case examples and empirical evidence, this article demonstrates how bankruptcy implementation in savings and credit cooperatives has become an effective instrument in facing financial crises and redirecting institutions toward sustainable growth. Practical implications and the potential expansion of bankruptcy concept utilization in microfinancial institutions are also discussed. In conclusion, bankruptcy implementation in savings and credit cooperatives is not only a response to financial challenges but also a powerful transformation tool for the empowerment of microfinancial institutions.